Effects of centerline rumble strips on safety, exterior noise, and operational use of the travel lane - Karkle, Daniel Edgard (Kansas State University, 2011)
Centerline rumble strips (CLRS) are effective in preventing cross-over crashes and are promoted in the United States (U.S.) as a low-cost safety measure. However, there may be negative issues and/or concerns that question their use under certain road conditions. This dissertation is the result of studying these issues and concerns to provide guidance to policy makers on future installations of CLRS, based on current good practices and on the results of specific investigations of exterior noise, safety effectiveness, economics, and drivers’ behavior, including their interaction with shoulders and shoulder rumble strips (SRS). From a survey conducted, good practices in the U.S. were summarized. From a before-and-after study of CLRS safety effectiveness, results showed that total correctable crashes were reduced by 29.21%. Crashes involving fatalities and injuries were reduced by 34.05%. Cross-over crashes were reduced by 67.19%, and run-off-the-road crashes were reduced by 19.19%. Both Naïve and Empirical Bayes methods were applied and showed statistically similar results. There was no statistical difference between football shaped and rectangular shaped CLRS. From the external noise study performed, it was found that external noise depends on vehicle speed, type of vehicle, and distance. Both football and rectangular CLRS substantially increased the levels of external noise at distances up to 45 m (150 ft). Therefore, before installing CLRS, the distance from houses or businesses should be considered. A distance of 60 m (200 ft) was recommended as the limit of the potential exterior noise problem area. From a study of drivers’ behavior, the analyzed configurations of rumble strips and shoulder width levels affected vehicular lateral position and speed levels, although speed deviations were not practically significant. The study of safety performance function models provided technical and economical recommendations for installation of CLRS. Overall, this study recommends the installation of CLRS on rural, two-lane, undivided rural roads in Kansas. Both patterns, rectangular and football, currently installed in Kansas have provided crash reductions, which have been reflected in economic benefits for society. Shoulder width and traffic volume should be considered as crash predictors for enhancement of the benefits. Guidelines were recommended for future better applications of CLRS.
Keywords: Centerline rumble strips; Transportation; Before and after analysis; Exterior noise; Driver behaviour; Industrial Engineering (0546); Transportation (0709)